2018
DOI: 10.18632/oncotarget.25257
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of squamous cell lung cancer with anaplastic lymphoma kinase (ALK)-rearrangement: a retrospective analysis and review

Abstract: Anti-anaplastic lymphoma kinase (ALK)-targeted therapy dramatically improves therapeutic responses in patients with ALK-rearranged lung adenocarcinoma (Ad-LC). A few cases of squamous cell lung carcinoma (Sq-LC) with ALK rearrangement have been reported; however, the clinicopathological features and clinical outcomes following treatment with ALK inhibitors are unknown. We addressed this in the present study by retrospectively comparing the clinical characteristics of five patients with ALK-rearranged Sq-LC wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 47 publications
1
19
0
1
Order By: Relevance
“…The DCR was 90.1% (10/11) and 25.0% (1/4), respectively ( p = 0.01). Four patients in which ALK rearrangement was assayed by IHC (−)/FISH (+) or IHC (+)/FISH (−) did not respond to crizotinib, and the duration time of treatment decreased sharply from one to four months ( p = 0.001) 26,27 …”
Section: Resultsmentioning
confidence: 99%
“…The DCR was 90.1% (10/11) and 25.0% (1/4), respectively ( p = 0.01). Four patients in which ALK rearrangement was assayed by IHC (−)/FISH (+) or IHC (+)/FISH (−) did not respond to crizotinib, and the duration time of treatment decreased sharply from one to four months ( p = 0.001) 26,27 …”
Section: Resultsmentioning
confidence: 99%
“…In the case reported here, there was no smoking history, basal ALK translocation was maintained, and MET amplification was found in addition to squamous cell transformation. Progression‐free survival of patients treated with crizotinib has been previously reported to be significantly shorter in squamous cell lung carcinoma with ALK rearrangement than in adenocarcinoma with ALK rearrangement 15 . This suggests that squamous cell histology can be related to resistance to ALK inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Crizotinib exhibited high response rates in advanced patients with ALK-positive NSCLC, especially brain metastasis [ 12 ]. In spite of the remarkable responses have been observed by some researchers [ 13 , 14 ], it is still controversy about the efficacy of ALK inhibitor in ALK-rearranged squamous cell carcinoma [ 9 ]. A recent study indicated that the RAS-RAF-MEK-ERK signaling pathway determines the ALK inhibitor response in ALK-positive lung cancer, but still needs further investigation [ 15 ].…”
Section: Discussionmentioning
confidence: 99%